The culture of letter-writing in pre-modern Islamic society - Gully, Adrian (Edinburgh University Press, 2008)
The Culture of Letter-Writing in Pre-Modern Islamic Society received an honourable mention from the British-Kuwait Friendship Society at BRISMES 2009 Writing letters was an important component of intellectual life in the Middle Islamic period, telling us much about the cultural history of pre-modern Islamic society. This book offers a unique analysis of letter-writing, focusing on the notion of the power of the pen. The author looks at the wider context of epistolography, relating it to the power structures of Islamic society in that period. He also attempts to identify some of the similarities and differences between Muslim modes of letter-writing and those of western cultures. One of the strengths of this book is that it is based on a wide range of primary Arabic sources, thus reflecting the broader epistemological importance of letter-writing in Islamic society. Key Features Evaluates the background to letter-writing as the principal representation of state documents and communication Takes a close look at the literary principles employed in that process Considers the important social and intellectual role of the secretary and how he fitted into the power structure of Islamic society during this period Argues that the voluminous collections of letters, written mainly in artistic prose, can be classified as an epistolary genre in their own right Shows that Islamic letter-writing was very culture-specific